Implementation and control of a hybrid boost DC-DC converter - Koh, Andy Jun Yang (2019)
This report describes the implementation and control of a hybrid boost DC-DC converter. The voltage regulation is carried out using two hysteresis-based sliding-mode controllers and a current-mode control being implemented. Different tests, such as the transient response, load change response, input voltage change response and reference voltage change response, were conducted and the performances of the different controllers were analysed. In addition, a comparison is performed to recommend the most suitable controller for the hybrid boost DC-DC converter.